Identification of characteristics of Russian students’ professional identity in the humanitarian, technical, and economic areas of training - O. I. Shcherbakova; V. P. Osipov (Вестник университета, 2024)
The purpose of this research work is to identify the features of the Russian students’ professional identity who study in humanitarian, technical, and economic areas of professional training. The theoretical analysis of scientific works, within the framework of which the problem of the Russian students’ professional identity is considered, has allowed us to conclude that most of them are static and isolated, and it largely affects the content of the results. An empirical study of the statuses of 245 students’ professional identity from the Plekhanov Russian University of Economics, based on the methodology of J.Е. Marcia, has provided an opportunity to use tools of descriptive and analytical statistics. Due to the frequency analysis of the results of the empirical study, predominance of the state of achieved identity in the overall structure of respondents has been revealed. However, in the course of a more detailed intergroup examination, through the Pearson’ chi-square test, it has been proven that along with the transition from “man – sign” specialties to “man – man” specialties, the number of students with the status of the achieved professional identity decreases. Meanwhile, the number of students who have moratorium of professional identity increases. The scientific novelty of this study lies in a comparative approach to the study of professional identity of students from higher educational institutions.